Federalism, an alternative to overcome the inequalities of sustainable development in the natural regions and macro regions of Peru - Coyla Zela, Mario Aurelio; Morales Rocha, José Luis; Lauracio Ticona, Teófilo; Ramos Rojas, Jarol Teófilo; Arroyo Japura, Gregorio; Vargas Torres, Nakaday Irazema (Frontiers in Sociology, 2023)
Political doctrines determine the formation of territorial units or geopolitical models more adequate to generate public value in subnational organizations, with positive results in the HDI, productivity indicators and national competitiveness oriented to improve the quality of public service for citizens who participate in democratic electoral processes with identity and that promote a decentralized State that does not generate development obstacles as an effect of geographical limits by departments and regional governments with inequalities in natural resources and comparative advantages, but that projects integration, better economic performance, sustainability, and sustainability for regional and national development and as an alternative to achieve political stability in Peru. The aim of this article is to explore whether the contribution of natural regions and macro-regions to sustainable development is unequal. Information from official web pages. The disparity index, analysis of variance (ANOVA) and Tukey's analysis were used. The GDP per capita of the coastal departments is 64% higher than that of the Andes and 136% higher than those of the Amazon; the HDI of the coast exceeds those regions by 31% and 19%; 44% of the urban population residing in marginal neighborhoods are on the coast, 67% in the Andes and 69% in the Amazon. The percentage of corruption is highest on the coast, followed by the Amazon. At the regional macro level, the primacy in GDP per capita and the HDI moves to the south, although the superiority of the corruption index persists in the center, followed by the south; both significantly higher than the east and north. This fact would reveal the possibility of a regional macro development without Lima and through axes of various development nodes, feasible in the era of globalization.